Determination of culinary properties of some potato varieties by sensorial analysis and polyphenoloxidase activity - Portela, Fábio (Pesquisa Agropecuaria Brasileira, 2014)
Polyphenoloxidase activity in water extract of four potato Solanum tuberosum varieties - three Brazilians: Chiquita, Mineira and Mantiqueira - and one from abroad - Bintje - was determined. Considering the results from sensorial analysis, it was concluded that only enzyme activity is not a measure of importance on breeding programs, selecting new varieties.